2018
DOI: 10.1113/jp275301
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lifelong exercise frequency on arterial stiffness

Abstract: Central arterial stiffness increases with sedentary ageing. While near-daily, vigorous lifelong (>25 years) endurance exercise training prevents arterial stiffening with ageing, this rigorous routine of exercise training over a lifetime is impractical for most individuals. The aim was to examine whether a less frequent 'dose' of lifelong exercise training (four to five sessions per week for > 30 min) that is consistent with current physical activity recommendations elicits similar benefits on central arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
111
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 40 publications
5
111
0
4
Order By: Relevance
“…; Shibata et al . ) imparted in middle age (Howden et al . ) has been demonstrated to induce substantial changes in cardiac compliance.…”
Section: Methodsmentioning
confidence: 99%
“…; Shibata et al . ) imparted in middle age (Howden et al . ) has been demonstrated to induce substantial changes in cardiac compliance.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, the relationships among arterial stiffness, ageing and exercise ‘dose’ were described in an article in The Journal of Physiology (Shibata et al . ). The authors sought to test the hypothesis that high lifelong exercise ‘dose’ (e.g.…”
mentioning
confidence: 97%
“…The study by Shibata et al . () in this issue of The Journal of Physiology investigated whether the frequency ‘dose’ of ‘lifelong’ habitual aerobic exercise training of 4–5 days week −1 for >30 min day −1 among MA/O adults, was sufficient to lower central artery stiffness compared with 2–3 days week −1 or <2 days week −1 . In a cross‐sectional study from the well characterized Cooper Centre Longitudinal Study, they studied four groups of MA/O adults who consistently reported the same level of regular aerobic exercise in repeated follow‐up exams over 20 or more years.…”
mentioning
confidence: 99%